Perancangan Program Animasi Interaktif Pengenalan Lagu Nasional Tingkat SD - Sayfulloh, Asep; Setiaji, Setiaji; Ishak, Riswandi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
Technological developments increased the more days as the development of modernization. Development of technology brought both positive and negative effects for some people. If we can learn the technological progress with both the technological advances that will have a positive impact, for example on education, not only the delivery of content using oral or written way but has been able to use audio-visual media. Technology can provide new lessons in the world of education by explaining how learning the national anthem of the primary level, not least those who are less eager to learn about the national anthem, so many children now do not know about the national anthem and the struggle of the heroes. The design was created using waterfall method is the method by analyzing, design, implementation, testing and operation of the hope of obtaining new knowledge as well as the information using Adobe Flash Professional CS6. One example application in this animation is learning the national anthem for a primary education is packed with interactive animations and audio visual so hopefully learning with interactive animations optimizing students' understanding of the national anthem, the animation is accompanied by an attractive image makes learning national songs more interesting and interactive.